2012
DOI: 10.1269/jrr.110142
|View full text |Cite
|
Sign up to set email alerts
|

Association of Computed Tomography-detected Pulmonary Interstitial Changes with Severe Radiation Pneumonitis for Patients Treated with Thoracic Radiotherapy

Abstract: We evaluated associations of interstitial changes with radiation pneumonitis (RP) for patients treated with thoracic radiotherapy. Between 2005 and 2009, patients who received thoracic radiotherapy of 40 Gy or more for lung cancer or thymic tumors and were followed-up for more than 6 months were eligible for this study. Possible risk factors for RP included the presence of interstitial changes on computed tomography before radiotherapy, and elevated C-reactive protein (CRP) and lactate dehydrogenase (LDH) leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 28 publications
6
38
0
1
Order By: Relevance
“…[7][8][9][10]12,33 In addition, pre-existing interstitial pneumonia is thought to be a risk factor for fatal RP after SBRT, 12,13 and has been reported in conventional radiotherapy. 34,35 Our results showed that the presence of ILD was a significant risk factor for both ≥ Gr2 RP and ≥ Gr3 RP; the incidences of ≥ Gr2 RP and ≥ Gr3 RP for those with ILD were 55.0% and 10.0%, respectively. Even minimal ILD change was a significant risk factor for ≥ Gr2 RP-the incidence was 50.0%-but not for ≥ Gr3 RP.…”
Section: Discussionmentioning
confidence: 66%
“…[7][8][9][10]12,33 In addition, pre-existing interstitial pneumonia is thought to be a risk factor for fatal RP after SBRT, 12,13 and has been reported in conventional radiotherapy. 34,35 Our results showed that the presence of ILD was a significant risk factor for both ≥ Gr2 RP and ≥ Gr3 RP; the incidences of ≥ Gr2 RP and ≥ Gr3 RP for those with ILD were 55.0% and 10.0%, respectively. Even minimal ILD change was a significant risk factor for ≥ Gr2 RP-the incidence was 50.0%-but not for ≥ Gr3 RP.…”
Section: Discussionmentioning
confidence: 66%
“…Other image parameters were previously found to be predictors of RP, such as RT dosimetric parameters mean lung dose, V5, V20, et cetera (25) and pre-RT CT interstitial findings (17,18). In this study, those dosimetric parameters did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Makimoto et al (17) found that pretreatment radiographic findings of underlying lung disease were associated with a higher incidence of RP (47.1% vs 5.3%, P < .001). Sanuki et al (18) found interstitial findings at CT were associated with grade 3 or higher RP (26% vs 3%, P < .001). Finding these subtle CT features requires an experienced chest radiologist.…”
mentioning
confidence: 97%
“…Patients with pre-existing ILD appear to be more susceptible to acute lung injury after RT, resulting in acute ILD exacerbation. It has been reported that for patients with pre-existing interstitial changes on computed tomography (CT), the incidence of RP ≥ grade 3 was significantly increased to 26% as compared to 3% for those with normal lung [26]. In another study, grade 4–5 RP occurred in 57% of patients with interstitial pneumonitis (IP) as compared to 2% of those without [27].…”
Section: Pre-existing Lung Diseasementioning
confidence: 99%